In Vitro Antibacterial Activity of Microbial Natural Products against Bacterial Pathogens of Veterinary and Zoonotic Relevance - Stefanie A. Barth; Daniel Preussger; Jana Pietschmann; Andrea T. Feßler; Martin Heller; Werner Herbst; Christiane Schnee; Stefan Schwarz; Florian Kloss; Christian Berens; Christian Menge (MDPI AG, 2024)
Antimicrobial resistance (AMR) is considered one of the greatest threats to both human and animal health. Efforts to address AMR include implementing antimicrobial stewardship programs and introducing alternative treatment options. Nevertheless, effective treatment of infectious diseases caused by bacteria will still require the identification and development of new antimicrobial agents. Eight different natural products were tested for antimicrobial activity against seven pathogenic bacterial species (Brachyspira sp., Chlamydia sp., Clostridioides sp., Mannheimia sp., Mycobacterium sp., Mycoplasma sp., Pasteurella sp.). In a first pre-screening, most compounds (five out of eight) inhibited bacterial growth only at high concentrations, but three natural products (celastramycin A [CA], closthioamide [CT], maduranic acid [MA]) displayed activity at concentrations <2 µg/mL against Pasteurella sp. and two of them (CA and CT) also against Mannheimia sp. Those results were confirmed by testing a larger collection of isolates encompassing 64 Pasteurella and 56 Mannheimia field isolates originating from pigs or cattle, which yielded MIC90 values of 0.5, 0.5, and 2 µg/mL against Pasteurella and 0.5, 4, and >16 µg/mL against Mannheimia for CA, CT, and MA, respectively. CA, CT, and MA exhibited higher MIC50 and MIC90 values against Pasteurella isolates with a known AMR phenotype against commonly used therapeutic antimicrobial agents than against isolates with unknown AMR profiles. This study demonstrates the importance of whole-cell antibacterial screening of natural products to identify promising scaffolds with broad- or narrow-spectrum antimicrobial activity against important Gram-negative veterinary pathogens with zoonotic potential.